Identifikasi Faktor yang Memengaruhi Indeks Pembangunan Manusia di Sulawesi Selatan (Makassar, Parepare, Palopo, dan Luwu Timur) Tahun 2010–2024 Menggunakan Fixed Effect Model - Fausiah, Putri Nur; Rahim, Abd; Astuty, Sri; Rajab, Abd; Syafri, Muhammad (Jurnal EMT KITA, 2026)
This study aims to analyze the effect of economic growth, unemployment rate, and poverty rate on the Human Development Index (HDI) in South Sulawesi Province, focusing on four regions, namely Makassar City, Parepare City, Palopo City, and East Luwu Regency during the period 2010–2024. The study uses panel data sourced from the Central Statistics Agency (BPS) and analyzed using the Fixed Effect Model (FEM). The number of panel observations is 60 (4 regions × 15 years). The estimation results show that economic growth has a negative and significant effect on the HDI, the unemployment rate has a positive but insignificant effect, while the poverty rate has a negative and significant effect on the HDI. Simultaneously, all three independent variables have a significant effect on HDI. These findings indicate that economic growth in the study area tends to be non-inclusive, thus failing to improve the quality of human development. Policy implications emphasize the importance of pro-poor growth strategies and increased investment in the education and health sectors.